Comparison of the treatment efficacies of HIFU, HIFU combined with GnRH-a, and HIFU combined with GnRH-a and LNG-IUS for adenomyosis: A systematic review and meta-analysis - Otgontuya, Altangerel; Jeng, Cherng-Jye; Wu, Trong-Neng; Chuang, Linus T; Shen, Jenta (Taiwanese journal of obstetrics & gynecology, 2023)
AbstractTo compare the treatment efficacies of high-intensity focused ultrasound (HIFU), HIFU combined with gonadotrophin-releasing hormone agonist (GnRH-a), and HIFU combined with GnRH-a and levonorgestrel-releasing intrauterine system (LNG-IUS) for adenomyosis. We conducted a literature search in SCIENCE DIRECT, COCHRANE LIBRARY, WILLEY ONLINE LIBRARY, PUBMED, and TAYLOR FRANCIS. A total of 471 articles identified, 12 were included in a systematic review, and 11 of them deemed quantitively eligible included in the meta-analysis. The efficacies of the three treatment regimens were assessed using the dysmenorrhea and menstrual scores at 3, 6, 12, 24 months. Of the three regimens, HIFU combined with GnRH-a and LNG-IUS provides the best outcome. On dysmenorrhea score at 6 months there was significantly different higher heterogeneity with P < 0.00001 (I 2 = 100% WMD 21.44 [6.34, 36.53]) with statistical significance P = 0.005. At 12 months there was significantly different higher heterogeneity P < 0.00001 (I 2 = 100% WMD 23.47 [6.00, 40.94]) with statistically significant P < 0.008. At 24 months there was significantly different higher heterogeneity P < 0.0005 (I 2 = 92% WMD 6.05 [4.81, 7.30]) with statistical significance P < 0.00001. HIFU combined with GnRH-a and LNG-IUS on menstrual score at 3 months was significantly different higher heterogeneity with P < 0.00001 (I 2 = 100% WMD 56.23 [16.01, 96.45]) with statistical significance P = 0.006. At 6 months there was significantly different higher heterogeneity P < 0.00001 (I 2 = 99% WMD 93.86 [64.15, 123.57]) with statistical significance P < 0.00001. At 12 months there was significantly different higher heterogeneity P < 0.00001 (I 2 = 99% WMD 97.13 [67.81, 126.46]) with statistical significance P < 0.00001 compared to treatments with only HIFU and HIFU combined with GnRH-a. HIFU combined with GnRH-a and LNG-IUS treatment is more effective than only HIFU monotherapy and HIFU combined with GnRH-a.